Effectiveness of indoor environmental quality in green building system / Mohd Anas Mohamad Rozmi - Mohamad Rozmi, Mohd Anas (Faculty of Architecture, Planning and Surveying, 2015)
Environment Quality Evaluation closed (IEQ) in Green Building system: A case study is an initiative undertaken to determine the effectiveness of IEQ in green building. Green building is an environmentally sustainable building, designed, built and operated to reduce the amount of environmental impact. Thus to achieved the objectives of the building to meet the benchmarks of the GBI standard, this study investigates the effectiveness of green building based on occupant satisfaction and indoor environmental quality analysis according to the Green Building Index (GBI) and the Malaysian Standard MS1525. The respondents were drawn from staffs in the building. Both methods involved qualitative and quantitative aspects which are questionnaire survey and analysis field measurement of Indoor Environmental Quality (IEQ).IEQ confirmed the results of the six parameters such as temperature, relative humidity, lighting, and C02 level are measured. The areas of case study of this dissertation in the Klang Valley, Selangor. The effectiveness of IEQ in Green Building can affect overall comfort of the building. The effectiveness of indoor environment (IEQ) in the Commercial Green Building are not followed the prescribed standard such as the reading of humidity, temperature and lighting.